Streamlining assessment and analysis of the effectiveness of engineering and logistics enterprise - Victoria Pekhtereva (Cхід, 2013)
The article suggests a conceptual approach to the improvement of methods of estimation and analysis of the effectiveness of enterprise's engineering support, cycle "science-engineering-production", which take part in the implementation.